Morphological study pollen grain belong to cultivated spp. of the family Fabaceae grown in Baghdad University campus/ Jadiriya. - Abo AL-Timen, Russull; AL Musawi, Ali (Iraqi Journal of Science, 2023)
Palynological characters of eleven cultivated species of the family Fabaceaegrown in Baghdad University campus has been presented in this work. The studyincluded two kind of single pollen grain. Tri.colporate in Bauhinia variegata L.,Cassia fistula L., Lablab purpureus(L.)sweet, Vigna mungo(L.)Hepper , and Tri-Colpate in Cassia acutifolia L., Mimosa pudica L., Vigna sinensis/L. Vicia faba L.,and polyad in Acasia cyanophylla Lindl, Acasia famesiana(L.)wild, Albizia lebbeck(L.)Benth.,A study focused on the shape of colpi and endoaperture are variable,shape of pollen show variation in polar and equatorial view for single species andfor front and side view for polyad one, The study determind size of pollen grain verysmall, medium and large in size. Pollen wall ornamentation was distinct in to twokinds Reticulate and Striate with variation among each group of the species.Depending on what has been mentioned above, it was found that these characters aretaxonomically important